Fresh and hardened properties of self-compacting concrete using metakaolin and GGBS as cement replacement - Abdallah Al-Oran, Abdallah Adnan; Safiee, Nor Azizi; Mohd. Nasir, Noor Azline (Taylor & Francis, 2019)
Self-compacting concrete (SCC) is a modern high-performance concrete, which is characterised by excellent performance in flowing and filling ability which required a high amount of cement. Nowadays there are many alternative materials, which possible to be used as a replacement of cement to overcome the negative effect due to the usage of cement such as ground granulated blast furnace slag (GGBS) and metakaolin (MK). This study aimed at investigating the fresh and hardened properties of SCC produced by GGBS and MK as partial cement replacement. Cement was replaced with MK at a constant level of 10% while GGBS is substituted cement at various levels of 15%, 20%, 25% and 30% as a ternary blending powder. Results obtained indicates that the inclusion of MK reduced the workability, oppose finding for GGBS exhibited improvement in the workability. For the hardened properties at an early age, mix which contained MK showed improvement in the strength characteristics, whilst at later age the mix with a combination of MK and GGBS exhibited better performance. From this study, it can be concluded that the optimum replacement level of cement to produce good quality of SCC is 10% and 25% for MK and GGBS, respectively.